Microstructure and Properties of Semi-Solid Al Alloy 7075 after Heat Treatment - Narissara Mahathaninwong (Prince of Songkla University, 2013)
Thesis (Ph.D. (Materials Engineering))--Prince of Songkla University, 2012.